Stability Investigations For Tailings Dams - J. C. Osler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1972)
The design of a tailings dam is a geotechnical engineering project of considerable scope. For the design, it is necessary to establish the engineering properties of the soil or rock strata which will support the dam and the tailings or other fill which will be used to construct the dam. The various field and laboratory investigations which are necessary to obtain the required design parameters are discussed in the paper and the use of these parameters to compute stability, settlement, and seepage are considered. The designer of a tailings dam can never assume an absolute knowledge of the properties of the foundation strata. Further, initial design assumptions are often approximate, particularly with regard to the distribution of pore pressures through and beneath the dam. Thus, the installation of performance monitoring instruments is recommended, since data obtained from such instrumentation can be used to check the stability of the structure both during construction and after its completion.